Risk Factors for Hospitalization After Dog Bite Injury: A Case‐cohort Study of Emergency Department Visits. (February 2014) - Rhea, Sarah; Weber, David J.; Poole, Charles; Cairns, Charles; Mello, Michael J.
Abstract Objectives Dog bite injuries may result in pain, infection, emotional distress, dysfunction, and disfiguration, as well as lead to costly health care utilization, such as emergency department (ED) visits, rabies postexposure prophylaxis, and hospitalizations. Although clinical care guidelines exist, to our knowledge risk factors for hospitalization after a dog bite injury have not been examined quantitatively. Quantifying the magnitude of association between modifiable risk factors, such as infection, and hospitalization after a dog bite injury may guide intervention efforts, improve patient outcomes, and reduce unnecessary hospitalizations. Methods A case‐cohort study was conducted to examine the association between the following risk factors and hospitalization: infection, complicated injury, host‐defense abnormality, number of previous evaluations for the injury, and anatomic location of the bite. The case‐cohort design was chosen because cases could be identified in a well‐defined administrative cohort, medical record review was required for each study patient, and the risk ratio was the effect measure of interest. The cohort consisted of ED patients evaluated for dog bite injuries between January 1, 2000 and December 31, 2011, at a large academic medical center. Cases were cohort members who were admitted as inpatients directly from the ED. From the cohort, a simple random sample was selected for the subcohort comparison group. Data on risk factors, the outcome, and covariates were collected from ED medical records. Logistic regression models, informed by directed acyclic graphs, were used to describe the relationship between each risk factor and hospitalization. Effect measure modification was examined by patient sex and race for the relationship between previous evaluation for the dog bite injury and hospitalization. Results Cases (n = 111) were more likely to be male, white, or insured by Medicaid than were members of the subcohort (n = 221). The most common type of complicated injury was tendon or ligament injury for cases and fracture for the subcohort. All factors evaluated were associated with increased risk of hospitalization after dog bite injury. Yet, infection at the time of ED visit (odds ratio [OR] = 7.8, 95% confidence interval [CI] = 3.8 to 16.0) and injury to multiple anatomic locations (OR = 6.0, 95% CI = 1.2 to 30.9) were associated with the largest relative risks of hospitalization. For every three ED visits for infected dog bites, one resulted in hospitalization. Having had one or more prior evaluations for the dog bite injury was associated with a lower risk of hospitalization for females than males and for whites than nonwhites. Conclusions This study provides a unique, quantitative examination of risk factors for hospitalization after dog bite injury. The relative risk of hospitalization associated with each factor was substantial. The strongest association was for a modifiable risk factor, infection. This finding may inform best practices for initial care of patients with dog bite injuries and the development of novel protocols for following patients to reduce infections and subsequent hospitalizations.